High dose, short course prednisolone for acute idiopathic thrombocytopenic purpura (ITP) in children - Jayaraman, Aparna; Das, Sarthak; Biswal, Niranjan; G., Dillikumar C.; Bade, Bhavna Ashok (International Journal of Contemporary Pediatrics, 2017)
Background: Immune thrombocytopenia (ITP) is a relatively benign and self-limiting condition. Though its dramatic presentation with skin or mucosal bleeds could be worrisome, the incidence of serious bleeding like intracranial hemorrhage (ICH) is relatively low (<1%) occurs at a very low count of <20,000 /mm3. The aim of the study was to compare a high dose, short course prednisolone with conventional Prednisolone therapy in the treatment of acute ITP of childhood. Methods: 20 cases and 18 retrospective controls with acute ITP were enrolled. The study group received 5mg/kg/day of oral prednisolone for four days. All the controls had received 2mg/kg/day of oral prednisolone for 14 days, tapered and stopped over the third week. Results: The study group was found to have significant decrease in clinical bleeding, (p=0.02), and significant increase in platelet count by day 3 of treatment (p=0.03) but no significant difference in platelet counts on day 7 of treatment (p=0.07) when compared with the control group. Conclusions: We conclude that the high dose short course oral prednisolone is significantly better than the conventional regimen in reducing clinically significant bleeding and raising the platelet count to safe levels within first 72 hours of therapy.